Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/ico.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Tear Film Osmolarity and 2 Different MMP-9 Tests With Common Dry Eye Tests in a Cohort of Non–Dry Eye Patients

Abstract: Similar to corneal staining, the MMP-9 is likely a late-stage sign that is rarely overexpressed in mild subjects, whereas tear osmolarity tends to be a more frequent early indicator of ocular surface disequilibrium within mild subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 24 publications
4
44
0
1
Order By: Relevance
“…The authors further reported a significant correlation between InflammaDry result and MMP-9 level 21. Likewise, we reported a Cohen κ coefficient of 0.921 signifying excellent agreement between InflammaDry result and MMP-9 level based on levels >40 ng/mL.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The authors further reported a significant correlation between InflammaDry result and MMP-9 level 21. Likewise, we reported a Cohen κ coefficient of 0.921 signifying excellent agreement between InflammaDry result and MMP-9 level based on levels >40 ng/mL.…”
Section: Discussionsupporting
confidence: 80%
“…Chotikavanich et al 12 reported a positive correlation between OSDI and tear MMP-9 level in patients with mild to severe dry eye, but Schargus et al 21 did not find any significant correlation between OSDI and tear MMP-9 level in patients with mild disease only. The authors further reported a significant correlation between InflammaDry result and MMP-9 level 21.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…More recently, Schargus et al have evaluated the performance of MMP-9 using InflammaDry (and confirmed by ELISA) and tear film osmolarity (TFO) tests in a cohort of 20 elderly patients with potential dry-eye disease, finding a positive association only between MMP-9 and corneal staining. However, MMP-9 has been rarely overexpressed in subjects with a mild syndrome (83).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A point-of-care test for the measurement of the concentration of MMP-9 in the tear film of patients suspected of DTS is available [18,67]. Because of a requirement for MMP-9 levels to be greater than 40 ng/ml to provide a positive assessment using the point-of-care diagnostic, the use of MMP-9 as a diagnostic measure may be valid only for patients with more severe forms of DTS [68]. …”
Section: Diagnostics and Clinical Assessmentsmentioning
confidence: 99%